Leptin into the ventrolateral medulla facilitates chemorespiratory response in leptin-deficient (ob/ob) mice - Bassi, M. [UNESP]; Furuya, W. I. [UNESP]; Menani, José Vanderlei [UNESP]; Colombari, Débora Simões de Almeida [UNESP]; Carmo, J. M. do; Silva, A. A. da; Hall, J. E.; Moreira, T. S.; Wenker, I. C.; Mulkey, D. K.; Colombari, Eduardo [UNESP] (Wiley-Blackwell, 2014)
AimLeptin, an adipocyte-derived hormone, is suggested to participate in the central control of breathing. We hypothesized that leptin may facilitate ventilatory responses to chemoreflex activation by acting on respiratory nuclei of the ventrolateral medulla. The baseline ventilation and the ventilatory responses to CO2 were evaluated before and after daily injections of leptin into the retrotrapezoid nucleus/parafacial respiratory group (RTN/pFRG) for 3days in obese leptin-deficient (ob/ob) mice.MethodsMale ob/ob mice (40-45g, n=7 per group) received daily microinjections of vehicle or leptin (1g per 100nL) for 3days into the RTN/pFRG. Respiratory responses to CO2 were measured by whole-body plethysmography.ResultsUnilateral microinjection of leptin into the RTN/pFRG in ob/ob mice increased baseline ventilation (V-E) from 144796 to 2405 +/- 174mLmin(-1)kg(-1) by increasing tidal volume (V-T) from 6.4 +/- 0.4 to 9.1 +/- 0.8mLkg(-1) (P<0.05). Leptin also enhanced ventilatory responses to 7% CO2 (=2172 +/- 218mLmin(-1)kg(-1), vs. control: =1255 +/- 105mLmin(-1)kg(-1)), which was also due to increased V-T (=4.71 +/- 0.51mLkg(-1), vs. control: =2.27 +/- 0.20mLkg(-1)), without changes in respiratory frequency. Leptin treatment into the RTN/pFRG or into the surrounding areas decreased food intake (83 and 70%, respectively), without significantly changing body weight.ConclusionThe present results suggest that leptin acting in the respiratory nuclei of the ventrolateral medulla improves baseline V-E and V-T and facilitates respiratory responses to hypercapnia in ob/ob mice.
Keywords: breathing; central chemoreception; leptin; obesity; ventrolateral medulla